Development of a Model for Developing Industrial Technician Teachers the Competencies in Academic Leadership - Lutthirom, Autsanun; Chianchana, Chaiwichit; Oungthong, Metha (Ratchaphruek Journal, 2026)
This research aimed to: 1) examine the competencies of industrial technician teachers; 2) investigate methods and processes for developing their academic leadership; and 3) develop a competency development model for industrial technician teachers in academic leadership. The study employed the Ethnographic Delphi Futures Research (EDFR) technique. The sample was purposively selected and consisted of experts. In the first round of structured interviews, two expert groups participated: seven higher education scholars and seven vocational education administrators, totaling 14 participants. In the second and third rounds, three groups were involved: seven higher education scholars, 11 vocational education administrators, and four vocational teachers, with a total of 22 participants. The research instruments included structured interview protocols developed from document analysis and related studies, and a five-point Likert scale questionnaire. Data were analyzed using the median and interquartile range. The findings revealed two key results. First, the study of the components of the competency development model for industrial Technician teachers in academic leadership identified five main elements: self-development, vision development, curriculum and instructional development, learning resource and classroom management, and learner quality development towards standards. Second, the developed model comprised 5 main components, 40 sub-components, and 53 indicators. Experts from all three groups reached consensus that the model was appropriate at the highest level.